Dualisme pendidikan umat Islam di Malaysia: sejarah, perkembangan dan cabaran masa depan - Hashim, Rosnani (Kolej Dar-al-Hikmah, 2002)
Dualistic system of education is a commonplace phenomenon for any nation that has been colonized by the western power, and Malaysia, once under the British rule is not an exception. With the introduction of Western education in the beginning of early 19th century, the existing religious education was sidelined and later supplanted with secular education. This present paper attempts to trace the origin of secular education by focusing the discussion of the concept of dualism in education. By “dualism” it means that there are two systems of education that run parallel as in this case: the religious and the secular system. This paper attempts to provide as overview on the genesis of dualism in education in the post-independence Malaysia, its challenges and its prospects. In the period of late 70s and early 80s Malaysia had witnessed an Islamic resurgence, culminating in the implementation of Islamization policy by the government. As a result of this there was a great demand for Islamic school system of education. This means the already existing National Education School System has to accommodate an increase in number of such schools popularly known as SMKA. Aside from this there are already numerous public religious school known as SAR which are also in great demand. The reality is that, with the increase in both structure and content of the Islamic school system does not change the status of dualism, rather it reinforces its dualistic nature. The present writer argues that so long there is no attempt to narrow the gap between the so-called religious and secular school system, the hope for an integrated, holistic system of education will not prevail. There s yet other issues added to this. The present vernacular system at the primary levels such as the Chinese and the Tamil Primary School (SRJK) would certainly pose an obstacle for the integration. Thus, the present writer, as a matter of national interest and as advocate of integrated school system of education concludes the paper with some practical suggestions, for the realisation of integrated system of education.